Moderatisme Pendidikan Islam Perspektif Dr. KH. Afifuddin Dhimyati dalam Tafsir Hidayatul Qur’an - Achmad Ichwan Basyar; Muhammad Shohib (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the concept of Islamic educational moderation from the perspective of Dr. KH. Afifuddin Dhimyati in Tafsir Hidayatul Qur’an and its implications for the development of Islamic education in Indonesia. This research employs a descriptive qualitative approach with a library research design. The primary source is Tafsir Hidayatul Qur’an fi Bayani Ma’ani Al-Qur’an, analyzed using content analysis. The findings reveal that Islamic educational moderation in Dr. KH. Afifuddin Dhimyati’s thought is constructed through the consistent application of the tafsir al-Qur’an bi al-Qur’an method. Moderation is understood as a proportional and balanced approach that harmonizes text and context without compromising fundamental Islamic principles. The key values include tawassuth (middle path), tawazun (balance), ‘adalah (justice), and tasamuh (tolerance). Its implications for Islamic education involve strengthening the integration of moderation values into the curriculum, reinforcing character formation through traditional learning methods, and developing an inclusive and contextual educational paradigm oriented toward the public good at both national and global levels